(untitled) (Italian Journal of Public Health, 2005)
Background. Food contamination by trichothecene mycotoxins is considered to be an emerging public health problem. The aim of this study was to validate a rapid sonification protocol, previously set up for cereal Fusarium DNA extraction from fast food samples, produced by a centre for research and development in the food industry in Catania, Sicily, and to validate it for a diagnostic PCR assay targeted at tri5, the key gene of trichothecene biosynthesis. Methods. DNA from reference Fusarium spp. strains and from fast food samples was prepared, setting up an extraction protocol adapted using some modifications based on a method recently described. Validation experiments were performed: serial dilution of DNA extracted from fungal cultures were added to food samples and then DNA was extracted. Specific primer pairs were used to detect F. graminearum and F. culmorum DNA in species-specific assays as well as trichothecene-producing Fusarium spp. in a group- specific system. Results. All genomic DNA extracted from trichothecene-producing Fusarium spp. as well as from DNA-spiked fast food samples and from food still in it’s original condition resulted in the correct amplification. The detection limit was 1 x 10-4 μg of DNA. All fungal and food samples tested gave highly consistent results in repeatability assays, thus demonstrating the within-lab and within/between-day precision of the method. Conclusions. Information on the epidemiology of trichothecene producing Fusarium through the food chain and the identification of the most frequently contaminated components of fast food are essential in order to develop effective public health strategies for minimising consumer exposure to trichothecenes.